2022
DOI: 10.1186/s12876-021-02073-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoserine phosphatase as a prognostic biomarker in patients with gastric cancer and its potential association with immune cells

Abstract: Background Because of dismal prognosis in gastric cancer, identifying relevant prognostic factors is necessary. Phosphoserine phosphatase (PSPH) exhibits different expression patterns in many cancers and has been reported to affect the prognosis of patients with cancer. In this study, we examined the prognostic role of metabolic gene PSPH in gastric cancer based on the TCGA dataset and our hospital–based cohort cases. Methods We collected and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…GO enrichment analysis results showed that DAPs enriched in each pathway are involved in various structures and functions such as oxidative phosphorylation, energy production, aerobic respiration, protein binding and transmembrane transport, antioxidant and various enzyme activities (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). We also found the GO terms that we are concerned about that are closely related to lipid metabolism and lipogenesis: taking LDM vs. BM as an example, 6 DAPs clustered on lipid binding belonging to molecular functions, 9 DAPs aggregate in lipid metabolism processes in biological processes, lipid transport and lipid regulation processes each gather 2 DAPs.…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment analysis results showed that DAPs enriched in each pathway are involved in various structures and functions such as oxidative phosphorylation, energy production, aerobic respiration, protein binding and transmembrane transport, antioxidant and various enzyme activities (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). We also found the GO terms that we are concerned about that are closely related to lipid metabolism and lipogenesis: taking LDM vs. BM as an example, 6 DAPs clustered on lipid binding belonging to molecular functions, 9 DAPs aggregate in lipid metabolism processes in biological processes, lipid transport and lipid regulation processes each gather 2 DAPs.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of Kaplan–Meier plots derived from data on 1925 lung cancer patients clearly confirmed the strong oncogenic role of HK2, LDHA, PHGDH, PSAT1, SHMT2, MTHFD2, c-Myc, and ATF4 (CREB-2) in lung cancer. The high expression of genes coding for all of these enzymes and their transcriptional regulators is strongly associated with a shortened patient survival in different types of malignancies [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSPH catalyzes the hydrolysis of 3-PS to produce serine. PSPH exhibits different expression patterns in many cancers and has been associated with the poor prognosis of patients with various cancers, including gastric cancer 51 . However, little is known about the role of PSPH in patients with glioblastoma.…”
Section: Discussionmentioning
confidence: 99%